Reference values for the 6-Min Walking Test in obese subjects. (July 2013) - Capodaglio, Paolo; De Souza, Shirley A.; Parisio, Cinzia; Precilios, Helmer; Vismara, Luca; Cimolin, Veronica; Brunani, Amelia
<x xml:space="preserve">Abstract</x> Purpose: The 6-Min Walking Test (6MWT) is widely used to measure the performance in various chronic conditions, such as in obese subjects. Reference equations for predicting distance walked during 6MWT specifically in adult obese subjects are not available. The aim of the paper is to establish reference values for 6MWT in an adult obese population. Methods: 323 obese patients (body mass index: BMI > 30 kg/m2, age range 20–60 years) admitted to our hospital for multidisciplinary rehabilitation and weight reduction programs were evaluated using 6MWT, heart rate, blood pressure, oxygen saturation, anthropometric measurements and level of dyspnoea were considered as outcome measure. Results: Distance walked during the 6MWT was significantly correlated to age, gender and BMI. The proposed reference equation is: 6MWTm = 894.2177 − (2.0700 × ageyrs) − (51.4489 × gendermales = 0; females = 1) − 5.1663 × <inline-graphic xlink:href="ark:/27927/pgg21jkn24q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />BMIKg/m2. In the multiple linear regression analysis age, gender and BMI explained 48% of the total variance in 6MWT. The average difference between predicted and measured 6MWT values (11.33 ± 52.98 m) did not reach statistical significance and the correlation was significant (r = 0.698). Conclusions: A reference equation specific for the obese population was provided; it can be used as realistic benchmark in the rehabilitation setting to assess functional capacity, plan exercise intensity and monitor changes over time.